Os deveres jurídicos do Estado brasileiro na efetivação do direito à moradia adequada como critérios para a elaboração e implementação de políticas públicas habitacionais - Mirra, Ana Beatriz Ribeiro David Valery (2023)
The present dissertation aims at identifying Brazilian State’s legal duties in terms of enforcing the right to adequate housing, which must be observed by its institutions when designing and implementing public housing policies. Through qualitative examination of the legal treatment granted by binding global, regional and national legal instruments to the human and fundamental right to adequate housing, carried out with the use of the hermeneutics of International Human Rights Law, it is verified that the full effectiveness of the right to adequate housing demands the realization of its material and existential aspects. To this end, it is essential that Brazilian institutions comply with a series of obligations of progressive results and immediate behavior, defined by national and international legal norms of programmatic structure. In addition, and due to the hypervulnerability of several individuals who live in unconventional places, being, therefore, subject to the annihilation of their human dignity, it is also duty of Brazilian institutions to act immediately to enable said individuals with the access to the minimum essential core of the right to adequate housing, which is embodied in its existential aspect. Due to this set of obligations regarding results and immediate behavior, Brazilian institutions do not have a wide margin of discretion in the decision-making processes related to the formulation and execution of public housing policies, which must be conformed to the legal imperatives arising from the national and international norms that regulate the subject-matter